Assessment of Knowledge and Awareness Levels of Healthcare Professionals and Candidates on Dentoalveolar Injuries - Tahir Ataözden; Fikret Özgür Coşkun; Semanur Özüdoğru (Ankara University, 2022)
Purpose: To evaluate the knowledge and awareness levels about traumatic dental injuries of various healthcare professionals and candidates who may encounter dentoalveolar injuries. Material and Methods: In this study, A total of 160 people, consisting of 3rd, 4th, 5th year students (47) studying at Faculty of Medicine, 3rd and 4th year students (91) studying at School of Nursing, and emergency physicians, emergency and traumatology nurses, and otorhinolaryngologist and specialist nurses (22) attended. Participants were asked to answer the questionnaire forms sent in digital environment. Results: 82.3% of the participants stated the percentage of teeth and jaws affected by trauma to the head and facial area as 40‐60% or more. When asked about what to do when you encounter an avulsed tooth case, 50.9% of them stated that they will refer the patient to the dentist and 48.4% should be in the first half hour, 11.3% of them reimplanting the avulsed tooth. While 23.9% of the participants preferred sterile saline solution during the transportation of the avulsed tooth, 33.3% stated that they did not have any knowledge. In addition, 29.6% stated that it was possible to replace the permanent tooth in the avulse, 73.6% stated that it is appropriate to hold the crown part and insert it, 66% stated that if the tooth is broken, it is important to find the broken piece. 87.4% of the participants stated that it is important to participate in an educational program related to dental trauma and 85.5% of them want to participate in an educational program. Conclusion: Within the limits of this study; It was concluded that training programs to improve the knowledge and awareness levels of non-dentist healthcare professionals who may encounter dentoalveolar trauma are necessary.